2017
DOI: 10.1007/s00216-017-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

New sampling device for on-site measurement of SVOC gas-phase concentration at the emitting material surface

Abstract: The gas-phase concentration at the material surface (y ) is pointed out in the literature as a key parameter to describe semivolatile organic compound (SVOC) emissions from materials. This is an important input data in predictive models of SVOC behavior indoors and risk exposure assessment. However, most of the existing measurement methods consist of determining emission rates and not y and none allow on-site sampling. Hence, a new passive sampler was developed. It consists of a glass cell that is simply place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…and tris-(chloropropyl)-phosphate (TCPP) on borosilicate glass has also indicated the likely existence of a relationship between these compounds' volatility and their partition coefficients at 23 ˚C (Ghislain et al, 2017), a finding also observed for the partitioning behaviour of DINP, DEHP, BBP and DnBP over stainless steel at 25 ˚C (Liang and Xu, 2014a).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…and tris-(chloropropyl)-phosphate (TCPP) on borosilicate glass has also indicated the likely existence of a relationship between these compounds' volatility and their partition coefficients at 23 ˚C (Ghislain et al, 2017), a finding also observed for the partitioning behaviour of DINP, DEHP, BBP and DnBP over stainless steel at 25 ˚C (Liang and Xu, 2014a).…”
Section: Introductionmentioning
confidence: 74%
“…The efficiency of the washing procedure applied for transferring the DEP from the sample enclosure surface to the solvent solution prior to UV-Vis spectroscopic measurements was evaluated by four replicated experiments in which an accurate amount of DEP (5.60, 0.86, 0.79 and 0.76 mg) was added within a sample enclosure vial that was then sealed and allowed to stabilise at 60 ˚C for 13 h. Washing solutions were diluted accordingly to result in absorbances within the linear range of the calibration curve. From these, an average recovery efficiency of 105.95 ± 7.01 % was recorded, as further illustrated in Table S1 of the SI, which was considered excellent (Cao et al, 2016;Ghislain et al, 2017;Wu et al, 2017).…”
Section: Quantification Of Dep Adsorbed On Enclosure Surfacesmentioning
confidence: 86%
See 2 more Smart Citations
“…The areas in which the research has mainly been addressed during the last five years have regarded the use of commercially available coatings, as well as the development of new coatings and their application. Many studies have been conducted in indoor environments in order Separations 2019, 6, 54 3 of 44 to monitor exposure to volatile organic compounds (VOCs) and semivolatile organic compounds (SVOCs) that are released into the air by many activities [1][2][3], but also by used furnishing [4,5]. Commercially available (divinylbenzene/carboxen/polydimethylsiloxane) DVB/CAR/PDMS fiber has been successfully employed in a method for the simultaneous analysis of trihalomethanes (THMs) such as trichloromethane, bromodichloromethane, dibromochloromethane, and tribromomethane, in ambient air [1].…”
Section: Airmentioning
confidence: 99%